Facilitating Knowledge Transfer to Students Through Tayammum Trekathon in An Interactive Activities - Nurdalila A’wani Abdul Aziz; Mohd Zuhaifah Mohamed Jamil; Dzulfadli Rosli; Muhamad Firdaus Ab Rahman; Nur Nadia Fadhlina Daman Huri; Dania Kirana Nor Rahmat (Kolej PERMATA Insan, 2025)
5th Insan Junior Researchers International Conference 2024 (iJURECON 2024) : "STREAM for a better future”/ editors : Ahmad Fuad Mohamad Amin, Ahmad Bazli Ahmad Hilmi, Nurhidaya Mohamad Jan, Norazlina Subani 25-26 October 2024 Organized by : Kolej Permata Insan